Age Estimation Methods in Forensic Odontology - Phuwadon Duangto; Apirum Janhom; Sukon Prasitwattanaseree; Pasuk Mahakkanukrauh; Anak Iamaroon (Faculty of Dentistry, Universitas Indonesia, 2016)
Forensically, age estimation is a crucial step for biological identification. Currently, there are many methods with variable accuracy to predict the age for dead or living persons such as a physical examination, radiographs of the left hand, and dental assessment. Age estimation using radiographic tooth development has been found to be an accurate method because it is mainly genetically influenced and less affected by nutritional and environmental factors. The Demirjian et al. method has long been the most commonly used for dental age estimation using radiological technique in many populations. This method, based on tooth developmental changes, is an easy-to-apply method since different stages of tooth development is clearly defined. The aim of this article is to elaborate age estimation by using tooth development with a focus on the Demirjian et al. method.